Cold-formed steel design - Yu, Wei-wen, 1924- (Wiley, 2010)
Updated and expanded to reflect all the important developments that have occurred in the field over the past decade, this Fourth Edition of the classic text provides you with more of the detailed, up-to-the-minute technical information and expert guidance you need to make optimum use of this incredibly versatile material for building construction. Wei-Wen Yu and Roger LaBoube, respected authorities in the field, draw upon decades of experience in cold-formed steel design, research, teaching, and development of design specifications to provide guidance on all practical aspects of cold-formed steel design for manufacturing, civil engineering, and building applications. Throughout the book, they describe the structural behavior of cold-formed steel members and connections from both the theoretical and experimental perspectives, and discuss the rationale behind the AISI and North American design provisions.